Characterization of the Admission to Medical Sciences Studies in the Regular Daytime Course (2007- 2012) - José Emilio Caballero González; Benerando Sevilla Pérez; Luis Manuel Pérez Concepción (Medisur)
The current paper presents an analysis of the admission to medical and dentistry undergraduate studies from the 2007-2008 course to the 2012-2013 course. A continuous failure to fulfil the approved admission plan for each province was observed in medical degrees during the last six years whereas dentistry studies showed greater fulfillment. The major causes affecting such plan according the expert criteria are mentioned.